Orphan Medicinal Products for the Treatment of Pancreatic Cancer: Lessons Learned From Two Decades of Orphan Designation - Mulder, Jorn; van Rossum, Tobias; Mariz, Segundo; Magrelli, Armando; de Boer, Anthonius; Pasmooij, Anna M. G.; Stoyanova-Beninska, Violeta (Frontiers in Oncology, 2021)
Pancreatic cancer has a dismal prognosis and only a few treatment options are available. In the European Union, pancreatic cancer classifies as a rare disease, allowing drug developers to apply for orphan medicinal product (OMP) designation. The aim of this study was to provide more detail on OMPs for pancreatic cancer. All applications for OMP designation submitted to the EMA between 2000 and 2019 were identified. For each medicinal product that received an OMP designation, the mode of drug action, use of protocol assistance, and current life cycle status was determined. Fifty-two medicinal products received an OMP designation. At the time of submission, eighteen OMPs were at the non-clinical and 34 OMPs were at the clinical stage of development. At least fourteen kinds of mode of action were explored in the condition. For eighteen out of 52 OMPs protocol assistance was sought. At the time of data analysis, one OMP received marketing authorisation and 24 OMPs were ongoing in development. Many medicinal products for pancreatic cancer received an OMP designation and the majority of these products was already in the clinical stage of development. Nonetheless, the success rate of OMPs for pancreatic cancer that reach the market is low, and increasing this rate is something to aspire. Fortunately, development is still ongoing for a part of the OMPs, and a few developers are planning to submit a marketing authorisation application in the near future. This however does not guarantee success, as pancreatic cancer remains a difficult disease to treat. Developers are advised to make optimal use of incentives such as protocol assistance, establishing (early) dialogue between regulators and drug developers and to agree on important topics such as clinical trial design.